Moznosti pouzitia fluorochinolónových chemoterapeutík v ortopédii a traumatológii - Krcméry, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1991)
In the submitted review the authors analyze hitherto published results with the use of new antimicrobial chemotherapeutic drugs--fluoroquinolones in the treatment of infections of the bones, joints, soft tissues and also in the peroperative prophylaxis in orthopaedics and traumatology. Quinolones are one of the drugs of choice which may be successful in the treatment of staphylococcal and gram-negative chronic osteomyelitis which are resistant to classical treatment and also the drug of choice in the treatment of septic arthritis and ostitis.
Keywords: infekce v ráně; Arthritis, Infectious; Anti-Infective Agents; Wound Infection; periostitida; infekční artritida; Humans; Periostitis; antiinfekční látky; 4-chinolony; osteomyelitida; Osteomyelitis; 4-Quinolones; lidé